Efektivitas Instalasi Pengolahan Air Limbah Industri Gula Pt. X Di Kabupaten Kediri, Jawa Timur - Ummah, Muhimatul; Nurul Hidayah, Hefinka Anevia (Window of Health : Jurnal Kesehatan, 2018)
Sugar Industry X in processing liquid waste from sugar production activities by using Waste Water Treatment Plant (WWTP). As the years of IPAL performance increase, it is necessary to evaluate the effectiveness of IPAL performance. The purpose of this research is to know the treatment of liquid waste in Sugar Industry X. The method used in this research is descriptive observasional. This research uses primary data and secondary data. Primary data were obtained from interview and interim observation of secondary data from processing section in the form of inlet laboratory test result and IPAL outlet. Parameter of result of laboratory test analysis is pH, BOD5, COD, TSS, Sulfide, oil and fat. Sampling is conducted from July to October 2017. The results of this study are the average pH concentration 7. The Sugar Industry X IPAL works effectively in lowering the concentrations of BOD5, COD, TSS, Sulfide, oils and fats. The order of decrease of concentration of parameters are 97,90%; 97.51%; 78.80%; 99.80%; 28.81%. From the evaluation of wastewater at IPAL outlet shows that all parameters have met the quality standard of waste water for sugar industry based on East Java Governor Regulation No. East. 52 of 2014 and Minister of Environment Regulation no. 5 Year 2014.